Transformational Learning and Teacher Collaborative Communities - Dayna McComish; Jim Parsons (New Zealand Journal of Teachers' Work)
An abundance of literature on transformational learning and teacher professional learning communities (PLCs) exists; yet, few, in any, have linked the presence of one within the other. We believe Mezirow’s Transformational Learning Theory should be acknowledged as a viable theoretical framework for better understanding the power of how teachers work together. Evidence of its presence can be identified within the current school practices of PLCs and other collaborative activities. In this paper, we will first overview Mezirow’s theories of transformational learning and then attempt to show how the work of professional learning communities specifically and teacher collaboration generally provide a platform for transforming teachers’ understandings of pedagogy and their roles as teachers. After outlining the concept of transformational learning, we provide two specific research examples to support the existence and relational significance of Mezirow’s Transformational Learning Theory as it relates to advancing teacher practice through collaboration. We trust that our paper adds to a better understanding of why teachers believe collaboration with their peers represents their best professional learning.